Transformasi Digital: Kesiapan Generasi Z dalam Mengadopsi Teknologi Artificial Intelligence (AI) di Dunia Akuntansi - Ayuningtyas, Ni Putu Winda; Lubis, Syarif Hidayah; Makaba, Kharisma Austin (Prosiding, 2024)
This study aims to analyze the technology readiness of Generation Z accountants in adopting Artificial Intelligence (AI) technology using the Technology Acceptance Model (TAM). The research employs a quantitative approach involving 220 Generation Z accountant respondents in Batam City, selected through purposive sampling techniques. Data were collected via questionnaires utilizing a Likert scale and analyzed using Partial Least Square Path Modeling (PLS-PM) with Google Colaboratory in the R programming language. The findings indicate that technology readiness significantly influences Generation Z accountants' adoption of AI. Perceived usefulness has been proven to be the dominant factor driving technology adoption, while perceived ease of use does not have a significant impact. These findings underscore the importance of technology readiness and perceived benefits as primary drivers in AI acceptance. The study recommends enhancing training and education regarding AI usage in accounting to strengthen the readiness and interest of Generation Z accountants towards this technology.